Autoimmune skin diseases in multiple sclerosis - M. Roncero Riesco; A. Cabanillas Cabral; Y. El Berdei Montero (Neurology Perspectives, 2025)
Introduction: Autoimmune dermatological diseases have a prevalence greater than 2% in the general population, sometimes as a primary disorder and other times within a context of systemic involvement. Comorbidity with multiple sclerosis (MS) has been described, particularly in the case of psoriasis and bullous pemphigoid, and to a lesser extent in pemphigus vulgaris and other autoimmune skin diseases. Development: Psoriasis is the autoimmune skin disease for which the most evidence is available on this association, with increased risk in patients with MS. Both disorders probably have common pathophysiological mechanisms. The joint treatment of both diseases will depend on the degree of activity of each one, but in general, it is recommended for patients with MS and psoriasis to avoid interferons, teriflunomide, and anti-CD20 monoclonal antibodies, whereas fumarates and S1P receptor antagonists are recommended. TNF-α inhibitors are formally contraindicated in MS. In the case of bullous pemphigoid, pemphigus vulgaris, and other less common autoimmune dermatological diseases, the relationship with MS is not so clearly established, although an association between the first 2 and neurological diseases, including MS, has been described. Treatment is based on corticotherapy, and classic immunosuppressants or rituximab may be combined, which represent an alternative for joint treatment. Conclusions: Comorbidity between MS and autoimmune dermatological disorders, and especially psoriasis, requires a joint approach, avoiding treatments that may aggravate one or the other disorders. Resumen: Introducción: Las enfermedades dermatológicas autoinmunes presentan una prevalencia superior al 2% en la población general, a veces como patología primaria y otras dentro de un contexto de afectación sistémica. La comorbilidad con la esclerosis múltiple (EM) se ha descrito especialmente en el caso de la psoriasis y del penfigoide ampolloso, y en menor medida en el pénfig. vulgar y otras enfermedades cutáneas autoinmunes. Desarrollo: La psoriasis es la patología en la que existe más evidencia de asociación, con incremento del riesgo en los pacientes con EM. Probablemente ambos trastornos comparten mecanismos fisiopatogénicos. El tratamiento conjunto de ambas enfermedades dependerá del grado de actividad de cada una de ellas, pero en general se recomienda evitar en los pacientes con EM y psoriasis los interferones, la teriflunomida y los anticuerpos monoclonales antiCD20 y se recomiendan los fumaratos o los antagonistas del receptor de S1P. Los fármacos antiTNF están formalmente contraindicados en la EM. En el caso del penfigoide ampolloso, el pénfig. vulgar y otras enfermedades dermatológicas autoinmunes menos frecuentes la relación con la EM no está tan claramente establecida, aunque sí se ha descrito asociación entre los dos primeros con enfermedades neurológicas, entre ellas la EM. La base del tratamiento es la corticoterapia, pudiendo asociarse inmunosupresores clásicos o rituximab, que suponen una alternativa para el tratamiento conjunto. Conclusiones: La comorbilidad entre la EM y patologías dermatológicas autoinmunes, especialmente en el caso de la psoriasis, supone la necesidad de realizar un abordaje conjunto, evitando los tratamientos que puedan agravar uno u otro trastorno.